In vitro Evaluation of Curcumin and Quercetin in Combination on Oxidative Stress - Katrolia, Archita; Vedpal; Shukla, Vikesh Kumar; Singh, Rohit; Chandra, Sheenu; Raman, Rajeshkumar (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Flavonoids are the natural product belongs to an important class of plant secondary metabolites. They are polyphenolic compounds and known for decades as a potent natural antioxidant. Curcumin (flavonoid polyphenol) and quercetin (flavonol) both are popular natural antioxidants and contributes a major role as an individual in the treatment of oxidative stress. This research study is more focused in their combination effect against oxidative stress. Materials and Methods In this present research, we focused on hydro-alcoholic maceration of Curcuma longa rhizomes and Morinda citrifolia fruits to extract the curcumin and quercetin respectively. Also, their role in oxidative stress was studied using in-vitro techniques. Results The percentage (%) yield of hydro-alcoholic extract attained from Curcuma longa rhizomes and Morinda citrifolia fruits were found to be 23.06% and 21.08% respectively. Conclusion Additionally, through DPPH (2,2-diphenyl-l-picrylhydrazyl) and Lipid peroxidation (LPO) assay, it was observed that curcumin and quercetin in combination gives the highest antioxidant activity when compared with their individual response at same concentration.
Keywords: Authentication; Hydro-alcoholic maceration; Curcumin; Quercetin; Flavonoids; Oxidative stress